Penerapan Pendekatan Pendidikan Matematika Realistik untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas IV Sekolah Dasar - Goni, Agnes M. (Peneliti.net, 2023)
This research aims to improve the mathematics learning outcomes of class IV students at SDN VI Bilalang through a Realistic Mathematics Education approach. This research is action research. The research subjects were 23 students in class IV of SDN VI Bilalang, consisting of 7 boys and 16 girls. The research method uses the Kemmis and Mc model. Taggart. The research was carried out in two cycles. The techniques used for data collection are observation and test questions. The research results show that realistic mathematics can improve the mathematics learning process and outcomes of class IV students at SDN VI Bilalang. The increase in learning activities using the Realistic Mathematics approach can be seen at the end of cycle I, namely student activity reached 51.5%, then increased at the end of cycle II, namely student activity reached 87.6%. Improvements in student learning outcomes can be seen from the grades obtained by students. The number of students who achieved completeness in cycle I was 20 students or 86%, and in cycle II completion reached 21 students or 91.30%. Thus, it can be said that the application of a realistic mathematical approach can improve student learning outcomes